طلاق الغضبان عند ابن قيم الجوزية : دراسة تحليلية في ضوء الفقه الشافعي - تالية، بدرية (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
This study, entitled "Divorce in the State of Anger According to Ibn Qayyim al-Jawziyyah: An Analytical Study in the Light of al-Shafi'i Jurisprudence" contains five chapters. The first chapter is an introductory chapter which contours the thesis basics. The second chapter contains the definition of divorce, its legitimacy, its divisions, its pillars, and its conditions. The third chapter addresses the definition of the term anger with an indication of its grades from the Holy Quran and Sunnah, and it derives the provisions of the Divorce in state of anger from the evidence of previous and contemporary scholars. In the fourth chapter, the provision of divorce in state of anger, with view from al-Shafi'i and Ibn Qayyim are given by stating the textual and logical evidences. The discussion of such evidences is allocated in chapter five by weighting and reconciling the two views. The study examines the issue of divorce in the state of anger in the schools of Shafi'i and Ibn Qayyim. The selected book of Ibn Qayyim: "Ighathah al-Lahfan fi hukum talaq al-Ghadban" represents the opposing school of al-Shafi'i that sees divorce in state of anger as not effective. As the researcher is a follower of al-Shafi'i School, she tries to consolidate the issue and study it, from the books of Shafi'i. The researcher uses the inductive approach in the extraction of evidences. By stating the views and evidences of the two schools, the researcher concludes that all al-Shafi'i disciples produce the same judgment that indicates divorce in state of anger is acceptable and effective based on general evidences of divorce and by considering the explicit term. At the same time, al-Shafi'i's view considers the intent as well. On the other hand, Ibn Qayyim sees anger as a condition, if there is a cause there is a judge, and when the cause is away, there is no judgment. Thus, provision of divorce in the state of anger by al-Shafi'i and Ibn Qayyim do not contradict each other, if taking explicit divorce words and its intent into account. Then, the divorce is effective when the explicit word of divorce and its intent come together.